PROVIDING DISTANCE EDUCATION DURING THE WAR: THE EXPERIENCE OF UKRAINE - Lidia Londar; Marcus Pietsch (Інформаційні технології і засоби навчання)
The sphere of education is multidimensional, it forms economic, political, and cultural impacts on society. Interruption (or complete stoppage) of the educational process in emergency situations caused by natural disasters, epidemics, and man-made disasters, results in extremely negative social consequences for society. The most negative impact on education occurs in the context of the war, as students are deprived of opportunities to learn. Destroyed schools and forced displacement can result in students no longer being able to learn in their typical learning environments. Even for students who are not affected by flight and displacement, learning opportunities in war zones can be limited because of newly dangerous circumstances. In such cases, distance education can offer students the opportunity to use distance learning technologies even under extremely difficult and challenging conditions and, in this way, contribute to a stable learning environment for students in times of war. However, little is known about distance education, the conditions for ensuring the continuity of the learning process during wartime, and how educational systems can be prepared to provide distance learning opportunities in such adverse conditions. Therefore, we explore how Ukraine is using distance education during the Russian war against Ukraine, in particular, by introducing IT innovations in distance learning. We also analyze the impact of digital technologies and educational IT infrastructure on the viability of the educational process under unfavorable social conditions. In addition, by constructing an educational regression model, we investigate various factors that may have influenced students’ achievement before the war (e.g., the availability of computers for students and teachers, schools’ access to high-speed internet, etc.), and identify the relationships between these factors. Our findings provide the first insights into the social implications and how countries can prepare to create distance-learning opportunities for their students during wartime and highlight the relevance of IT infrastructure in this context.